2020
DOI: 10.1007/978-3-030-50309-3_42
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Insider Threat Attacks Using Natural Language Processing: Automatically Mapping Organic Narrative Reports to Existing Insider Threat Frameworks

Abstract: Traditionally cyber security has focused on defending against external threats, over the last decade we have seen an increasing awareness of the threat posed by internal actors. Current approaches to reducing this risk have been based upon technical controls, psychologically understanding the insider's decision-making processes or sociological approaches ensuring constructive workplace behaviour. However, it is clear that these controls are not enough to mitigate this threat with a 2019 report suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…• • Study of permafrost distribution in Sikkim Himalayas using Sentinel-2 satellite images and logistic regression modeling [45] • The efficiency of artificial neural networks for glacier ice-thickness estimation: A case study in the western Himalayas, India [46] • Sentiment analysis using machine learning: Progress in the machine intelligence for data science [47] • Fine-tuned convolutional neural network for different cardiac view classifications [48] • Insider Threat Detection Based on Natural Language Processing Word Embedding and Machine Learning [49] • Classification of botnet attacks in Internet of Things Using a Convolution Neural Network [50] • A survey of Convolution Neural Network based Network intrusion detection [51], natural language processing [48], and speech recognition [52].…”
Section: Deep Learningmentioning
confidence: 99%
“…• • Study of permafrost distribution in Sikkim Himalayas using Sentinel-2 satellite images and logistic regression modeling [45] • The efficiency of artificial neural networks for glacier ice-thickness estimation: A case study in the western Himalayas, India [46] • Sentiment analysis using machine learning: Progress in the machine intelligence for data science [47] • Fine-tuned convolutional neural network for different cardiac view classifications [48] • Insider Threat Detection Based on Natural Language Processing Word Embedding and Machine Learning [49] • Classification of botnet attacks in Internet of Things Using a Convolution Neural Network [50] • A survey of Convolution Neural Network based Network intrusion detection [51], natural language processing [48], and speech recognition [52].…”
Section: Deep Learningmentioning
confidence: 99%
“…Bowen et al [20] proposed a Decoy Document Distributor, D 3 , system which automatically generates and distributes decoy documents across a file system aimed at luring malicious users. The authors employed a rule-based approach to design the decoy documents.…”
Section: A Deception-based Approachesmentioning
confidence: 99%
“…The evaluation results indicated that the proposed approach successfully identified insiders in about 66.7% of all cases. More recently, Paxton et al [3] proposed a natural language processing framework to model incidents of insider attacks using written and recorded notes of an incident. Despite many years of research, the practical progress on this field is relatively slow due to the lack of data and limitations of the underling techniques.…”
Section: Content-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation